Red dichromatic imaging enhances submucosal visibility during endoscopic submucosal dissection: Pilot study - Ishikawa, Tsubasa; Tashima, Tomoaki; Kawasaki, Tomonori; Fujimoto, Kankei; Sugimoto, Kei; Shin, Takahiro; Muramatsu, Takahiro; Mashimo, Yumi; Ryozawa, Shomei (Endoscopy International Open, 2025)
In 2020, Olympus Medical Systems Corporation introduced red dichromatic imaging (RDI) as a novel image-enhanced endoscopy (IEE) technology. However, clinical evidence regarding its practical applications and the lesions for which RDI is beneficial remains limited. Endoscopic submucosal dissection (ESD) is an essential therapeutic option for gastrointestinal tumors, yet achieving clear visualization of the dissecting layer remains a significant challenge. This study aimed to evaluate the efficacy of RDI in enhancing visualization of the dissecting layer during ESD.A total of 86 images from 43 gastrointestinal tumors (esophagus, stomach, duodenum, colon, and rectum) were evaluated by eight endoscopists. Visibility of the dissecting layer was assessed using a scale ranging from -2 (poor) to 2 (excellent) under white light imaging (WLI) and RDI. In addition, the color difference between the submucosal and muscular layers was analyzed using the International Commission on Illumination Lab color space system.RDI significantly improved visibility of the dissecting layer compared with WLI. Moreover, RDI showed a significantly greater color difference between the submucosal and muscular layers than WLI.RDI enhances visualization during ESD by improving visibility of the dissecting layer and increasing color differentiation compared with conventional WLI. These findings suggest that incorporating RDI into routine endoscopic practice could lead to more precise and efficient ESD procedures, ultimately improving patient outcomes.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...); Quality and logistical aspects; Training